CADANGAN PREMI ASURANSI JOINT-LIFE DENGAN SUKU BUNGA TETAP DAN BERUBAH SECARA STOKASTIK - SUKANASIH, NI KOMANG; WIDANA, I NYOMAN; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 7 No 2 (2018)DO - 10.24843/MTK.2018.v07.i02.p188, 2018)
Joint life is an insurance that covered two or more individuals in one policy. This research aims to determine the value and comparison of  fixed deposit rate premium and stochastic rate with V asicek model. I t used prospective calculation method . The mortality table in the research used TMI-2011 , for participant were couple age 40 and 35 years old with 10 year premium payment. Under this condition the value of constant rate premium and Vasicek rate premium is  and . Besed of this research showed the value of the Vasicek rate premium is smaller than constant rate premium.